Anemia and malnutrition in geriatric hospitalized patients: a cross-sectional retrospective study - Elisabeth Lucia Zeilinger; Bärbel Sturtzel; Alexa Leonie Meyer; Jakob Pietschnig; Caterina Sturtzel; Julia Lehner; Chiara Popinger; Gerald Ohrenberger; Ibrahim Elmadfa; Matthias Unseld (BMC Geriatrics)
Abstract Background Nutritional factors contributing to anemia in older adults are in need of clarification. We investigated associations between nutritional biomarkers and the incidence of anemia. Methods A cross-sectional study was conducted in two centers. Data were collected from patients living in long-term care hospitals. The Geriatric Nutritional Risk Index (GNRI) was applied to determine nutritional risk. Blood parameters were obtained from medical records. Anemics vs. non-anemics were assigned according to hemoglobin levels following the WHO guidelines. Multiple linear regression analysis were performed for statistical analysis. Results The sample consisted of N = 97 geriatric patients (mean age 84.9 years, 86% female). Anemic patients had a significantly lower GNRI (M = 90.6 ± 5.94; p =.007) than non-anemic patients (M = 94.7 ± 6.11). Serum albumin (p =.008), blood iron (p <.001), number of erythrocytes (p <.001), and the hematocrit value (p <.001) were also significantly lower in patients with anemia. Multiple linear regression showed that serum albumin concentration, in addition to the hematocrit, was the driving factor for hemoglobin concentration in anemic patients (p =.004; R²=0.77). Conclusion The present study indicates that nutritional risk plays a substantial role in anemia development in older adults. These findings may be attributable to multifactorial metabolic pathways of macro- and micronutrients on blood hemoglobin concentration. Malnourished geriatric patients with anemia may benefit from a diet rich in protein and iron-rich foods.